Greener and rapid synthesis of benzal-based Schiff base ligands as an efficient antibacterial, antioxidant, and anticancer agent. Issue 4 (16th February 2023) - Saranya, G.; Devendraprasad, K.; Jayanthi, P.; Shanmugapriya, P.; Bhuvaneshwari, N.
Abstract: Using an ecologically friendly sonication protocol, certain benzal-based Schiff base ligands were produced by combining benzaldehyde and its para-derivatives with 2-(2-methoxyphenoxy)ethanamine. The reaction lasts around 2 min and yields 86.27% of the Schiff base ligands. Human tumor cell lines were used to test the ligand anticancer action and the results showed that MPEA-ANI (Antiproliferation of Breast cancer MDA MB 231 is 71% and Lung cancer A 549 is 85%) exhibits significant inhibition against both cell lines. Through the scavenging effects of ligands on DPPH, hydrogen peroxide, and nitric oxide radicals, the ligands antioxidant properties were investigated. The bacteria strains used to assess the antibacterial effectiveness of ligands were Bacillus subtilis, Staphylococcus aureus (Gram-positive bacteria), and Escherichia coli (Gram-negative bacterium). The ligands were described using elemental analysis, FT-IR, 1 H NMR, 13 C NMR, and mass spectroscopy. Graphical Abstract: UF0001